DIVERSITAS SERANGGA TANAH DI BERBAGAI TIPE TANAH PADA LAHAN REKLAMASI BEKAS TAMBANG KAPUR KABUPATEN TUBAN - Dwi Oktafitria; Dewi Hidayati; Eko Purnomo (Florea : Jurnal Biologi dan Pembelajarannya, 2019)
The purpose of this study was to determine the diversity of soil insect orders in the reclamation area of former limestone quarries in the top soil type, spoil and reject product used in the media for land reclamation processes. This research sampling technique uses a pitfall trap tool. This study used descriptive quantitative data analysis using the Shannon-Wiener diversity index, Simpson dominance index, Pielou species evenness index, and index of Morisista-Horn habitat similarity. Based on the research that has been done it can be concluded that the reclamation land in 2010 with the dominant type of dust has a low diversity category and a high dominance category with the discovery of 4 orders. The reclaimed land in 2014 with the dominant clay type soil has a moderate diversity category and a low dominance category with 7 orders found. Whereas the reclamation land in 2016 with the dominant type of sand has a low diversity category and a high dominance category with the discovery of 8 orders. The spread of species in all three locations was categorized evenly and between locations did not have the same community.